Grid-like Neural Representations Support Olfactory Navigation of a Two-Dimensional Odor Space - Bao, Xiaojun; Gjorgieva, Eva; Shanahan, Laura K.; Howard, James D.; Kahnt, Thorsten; Gottfried, Jay A. (Neuron (Cambridge, Mass.), 2019)
Searching for food, friends, and mates often begins with an airborne scent. Importantly, odor concentration rises with physical proximity to an odorous source, suggesting a framework for orienting within olfactory landscapes to optimize behavior. Here, we created a two-dimensional odor space composed purely of odor stimuli to model how a navigator encounters smells in a natural environment. We show that human subjects can learn to navigate in olfactory space and form predictions of to-be-encountered smells. During navigation, fMRI responses in entorhinal cortex and ventromedial prefrontal cortex take the form of grid-like representations with hexagonal periodicity and entorhinal grid strength scaled with behavioral performance across subjects. The identification of olfactory grid-like codes with 6-fold symmetry highlights a unique neural mechanism by which odor information can be assembled into spatially navigable cognitive maps, optimizing orientation, and path finding toward an odor source. •How the human brain supports navigation in an odorous landscape is poorly understood•Subjects learn to orient within a 2D intensity space defined by two different odors•Odor navigation elicits grid-cell-like activity in prefrontal and entorhinal cortices•Findings suggest a mechanism by which the brain constructs olfactory cognitive maps Grid cells in entorhinal cortex underlie spatial orientation and path finding. Bao et al. show that entorhinal grid-like codes with behavioral relevance emerge when humans mentally navigate an olfactory landscape, highlighting potential neural mechanisms for locating odor sources in odiferous environments.